Differentiation of propeptide residues regulating the compartmentalization, maturation and activity of the broad-range phospholipase C of Listeria monocytogenes - Slepkov, Emily R. (2010)
The intracellular bacterial pathogen Listeria monocytogenes secretes a broad-range phospholipase C enzyme called PC-PLC (phosphatidylcholine phospholipase C) whose compartmentalization and enzymatic activity is regulated by a 24-amino-acid propeptide (Cys(28)–Ser(51)). During intracytosolic multiplication, bacteria accumulate the proform of PC-PLC at their membrane–cell-wall interface, whereas during cell-to-cell spread vacuolar acidification leads to maturation and rapid translocation of PC-PLC across the cell wall in a manner that is dependent on Mpl, the metalloprotease of Listeria. In the present study, we generated a series of propeptide mutants to determine the minimal requirement to prevent PC-PLC enzymatic activity and to identify residues regulating compartmentalization and maturation. We found that a single residue at position P1 (Ser(51)) of the cleavage site is sufficient to prevent enzymatic activity, which is consistent with P1′ (Trp(52)) being located within the active-site pocket. We observed that mutants with deletions at the N-terminus, but not the C-terminus, of the propeptide are translocated across the cell wall more effectively than wild-type PC-PLC at a physiological pH, and that individual amino acid residues within the N-terminus influence Mpl-mediated maturation of PC-PLC at acidic pH. However, deletion of more than 75% of the propeptide was required to completely prevent Mpl-mediated maturation of PC-PLC. These results indicate that the N-terminus of the propeptide regulates PC-PLC compartmentalization and that specific residues within the N-terminus influence the ability of Mpl to mediate PC-PLC maturation, although a six-residue propeptide is sufficient for Mpl to mediate PC-PLC maturation.